2002
DOI: 10.7589/0090-3558-38.1.84
|View full text |Cite
|
Sign up to set email alerts
|

Causes of Mortality in Reintroduced Eurasian Lynx in Switzerland

Abstract: Seventy-two lynx, found dead in the Swiss Alps and the Jura Mountains (Switzerland) from 1987-99, were evaluated to determine the cause of death. Seventy-two per cent (52/72) of all animals died because of noninfectious diseases or causes such as vehicular collision and poaching. Eighteen percent (13/72) died from infectious diseases, including some which could have been transferred to the lynx from domestic animals or other wild animals such as panleukopenia and sarcoptic mange. If only radio-tagged animals (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
64
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(66 citation statements)
references
References 23 publications
2
64
0
Order By: Relevance
“…Detection biases can arise from the cause of death. For example, a study on Eurasian lynx showed that infectious diseases are underrepresented in animals found by chance while mortality resulting from anthropogenic activities is overrepresented [95]. The use of dogs has been shown to be an efficient method for increasing detection of diseased or dead animals, including medium-sized to small mammals particularly difficult to detect, and thus of decreasing bias in the recovered study material [96,97].…”
Section: Introductionmentioning
confidence: 99%
“…Detection biases can arise from the cause of death. For example, a study on Eurasian lynx showed that infectious diseases are underrepresented in animals found by chance while mortality resulting from anthropogenic activities is overrepresented [95]. The use of dogs has been shown to be an efficient method for increasing detection of diseased or dead animals, including medium-sized to small mammals particularly difficult to detect, and thus of decreasing bias in the recovered study material [96,97].…”
Section: Introductionmentioning
confidence: 99%
“…Except for sarcoptic mange, which commonly affects lynx in areas of endemic disease in red fox (Vulpes vulpes; Holt and Berg, 1990;Mö rner, 1992a;Ryser-Degiorgis et al, 2002), few isolated cases of infectious diseases have been reported in free-ranging Eurasian lynx. Notable disease reports include rabies (e.g., Fernex, 1976;Schneider et al, 1989;Stahl and Vandel, 1999;Tschirch, 2001), feline parvovirus (FPV) infections (Stahl and Vandel, 1999;Schmidt-Posthaus et al, 2002), Borna disease (Degiorgis et al, 2000), and notoedric mange (Ryser- Degiorgis et al, 2002). In captive individuals, feline infectious peritonitis (Hyslop, 1955) and a cowpox virus infection (M. Bennett, pers.…”
Section: Introductionmentioning
confidence: 99%
“…(Kazlauskas and Prusaite, 1976;Kazlauskas and Matusevicius, 1981;Schmidt-Posthaus et al, 2002;Bagrade et al, 2003;Valdmann et al, 2004). The prey preference of Eurasian lynx varies, depending on region and availability.…”
mentioning
confidence: 96%